Phylogenomic Analyses of Members of the Widespread Marine Heterotrophic Genus Pseudovibrio Suggest Distinct Evolutionary Trajectories and a Novel Genus, Polycladidibacter gen. nov - Hinger, I.; Ansorge, R.; Mussmann, M.; Romano, S. (Applied and environmental microbiology, 2020)
The genus Pseudovibrio is commonly associated with marine invertebrates, which are essential for ocean health and marine nutrient cycling. Traditionally, the phylogeny of the genus has been based on 16S rRNA gene analysis. The use of the 16S rRNA gene or any other single marker gene for robust phylogenetic placement has recently been questioned. We used a large set of marker genes from all available Pseudovibrio genomes for in-depth phylogenomic analyses. We identified divergent monophyletic basal lineages within the Pseudovibrio genus, including two strains isolated from polyclad flatworms. These strains showed reduced sulfur metabolism and biosynthesis capacities. The phylogenomic analyses revealed distinct evolutionary trajectories and ecological adaptations that differentiate the divergent strains from the other Pseudovibrio members and suggest that they fall into a novel genus. Our data show the importance of widening the use of phylogenomics for better understanding bacterial physiology, phylogeny, and evolution. Bacteria belonging to the Pseudovibrio genus are widespread, metabolically versatile, and able to thrive as both free-living and host-associated organisms. Although more than 50 genomes are available, a comprehensive comparative genomics study to resolve taxonomic inconsistencies is currently missing. We analyzed all available genomes and used 552 core genes to perform a robust phylogenomic reconstruction. This in-depth analysis revealed the divergence of two monophyletic basal lineages of strains isolated from polyclad flatworm hosts, namely, Pseudovibrio hongkongensis and Pseudovibrio stylochi . These strains have reduced genomes and lack sulfur-related metabolisms and major biosynthetic gene clusters, and their environmental distribution appears to be tightly associated with invertebrate hosts. We showed experimentally that the divergent strains are unable to utilize various sulfur compounds that, in contrast, can be utilized by the type strain Pseudovibrio denitrificans . Our analyses suggest that the lineage leading to these two strains has been subject to relaxed purifying selection resulting in great gene loss. Overall genome relatedness indices (OGRI) indicate substantial differences between the divergent strains and the rest of the genus. While 16S rRNA gene analyses do not support the establishment of a different genus for the divergent strains, their substantial genomic, phylogenomic, and physiological differences strongly suggest a divergent evolutionary trajectory and the need for their reclassification. Therefore, we propose the novel genus Polycladidibacter gen. nov. IMPORTANCE The genus Pseudovibrio is commonly associated with marine invertebrates, which are essential for ocean health and marine nutrient cycling. Traditionally, the phylogeny of the genus has been based on 16S rRNA gene analysis. The use of the 16S rRNA gene or any other single marker gene for robust phylogenetic placement has recently been questioned. We used a large set of marker genes from all available Pseudovibrio genomes for in-depth phylogenomic analyses. We identified divergent monophyletic basal lineages within the Pseudovibrio genus, including two strains isolated from polyclad flatworms. These strains showed reduced sulfur metabolism and biosynthesis capacities. The phylogenomic analyses revealed distinct evolutionary trajectories and ecological adaptations that differentiate the divergent strains from the other Pseudovibrio members and suggest that they fall into a novel genus. Our data show the importance of widening the use of phylogenomics for better understanding bacterial physiology, phylogeny, and evolution.